Noninvasive fetal genotyping of paternally inherited alleles using targeted massively parallel sequencing in parentage testing cases. Issue 6 (10th March 2017) - Yang, Donggui; Liang, Hao; Gao, Yu; Lin, Shaobin; He, Zhiming; Gao, Jun; Sun, Hongyu; Li, Qing; Ma, Xiaoyan; Ou, Xueling
Abstract : BACKGROUND: Researchers have sought to develop a noninvasive protocol for paternity analysis that uses fetal cell‐free DNA (cfDNA) in maternal plasma. Massively parallel sequencing (MPS) is expected to overcome this challenge because it enables the analysis of millions of DNA molecules at a single‐base resolution. STUDY DESIGN AND METHODS: Seven women were involved in prenatal paternity testing cases. Before conventional invasive procedures, cfDNA was isolated from maternal plasma. Fetal tissues were then collected, as were blood samples from the alleged fathers. A custom array was designed that targeted 1497 regions containing single‐nucleotide polymorphisms. These regions were massively parallel sequenced. RESULTS: In these seven cases, the mean nonmaternal allele fractions in maternal plasma ranged from 3.22% to 6.17%. Setting the allele fraction cutoff of 2.5%, 300 to 491 loci were considered informative for paternal origin and no genetic incompatibilities with the alleged fathers were found. These results were concordant with those of conventional short tandem repeat genotyping. Validation results performed using fetal samples showed that sequencing noise was completely filtered out, and 78.35% to 99.19% of the paternal alleles were accurately genotyped. The fetal cfDNA concentrations ranged from 7.12% to 13.81%, and the overall sequencing error rates ranged from 0.40% to 0.93%. CONCLUSION: In our study, we evaluate a straightforward method that can be used to identify paternal alleles based on analyses of paternal alleles and sequencing errors in maternal plasma. Our results support the notion that an MPS‐based method could be utilized in noninvasive fetal genotyping and prenatal paternity analyses.